Cu(II), Cd(II), Pb(II) and As(V) adsorption from aqueous solutions using magnetic iron-modified calcium silicate hydrate: Adsorption kinetic analysis. (April 2021) - Valenzuela, Fernando; Quintana, Geraldine; Briso, Alejandro; Ide, Viviana; Basualto, Carlos; Gaete, José; Montes, Gonzalo
Highlights: Acidic waters are decontaminated using a magnetic iron-modified adsorbent. Fe modification of a nanostructured calcium silicate improve the adsorption of As(V). Nanostructured calcium silicate removes ions via ion-exchange mechanisms. The adsorbent is chemically stable in aqueous solutions with a pH above 3.0. Abstract: The preparation and characterization of a solid adsorbent consisting of magnetic and iron-modified calcium silicate hydrate (mag-FeNanoCSH) was studied. The adsorbent, prepared using two kinds of magnetite (Fe3 O4 ), was evaluated for the simultaneous removal of cations and anions from synthetic aqueous mine water. The adsorbent synthesis was found to be very efficient and reproducible. SEM and TEM images showed that the adsorbent is formed by agglomerates of spherical particles with diameters between 20 nm and 170 nm. BET porosimetry analysis indicated that the resulting solid presents a specific surface area of 50−70 m 2 /g. VSM analysis confirmed that the particles exhibit a magnetic saturation between 33 emu/g and 64 emu/g, which is high enough to enable their separation from aqueous raffinates using common magnets. The adsorbents are chemically stable in aqueous solutions with pH values above 3.0. In this pH range, approximately 99 % of the Cu(II), Cd(II) and Pb(II) initially present in aqueous solution was removed via ion exchange and salt and/or hydroxide formation chemisorption mechanisms. Furthermore, the magnetic and Fe-modified calcium silicates enabled As(V) adsorption close to 98 % when a sufficient adsorbent dosage was used, forming very insoluble and stable salts that could be safely disposed of later. Using the mag-FeNanoCSH adsorbents, a high initial rate of ion adsorption was observed. The kinetics data are well explained by a pseudo-second-order kinetic model.